SPECIAL ISSUE ON REIMAGINING VISUAL ARTS, MEDIA, AND CULTURAL PEDAGOGY IN THE AGE OF ARTIFICIAL INTELLIGENCE - Bharadwaj, Kumkum; C. Govindaraj,; Reddy, R. Devarajulu; Walling, A. Wati; Jebakumar, A. Noble (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Dear Readers and Contributors, It gives me immense pleasure to present this special issue of ShodhKosh: Journal of Visual and Performing Arts (E-ISSN 2582-7472), titled Reimagining Visual Arts, Media, and Cultural Pedagogy in the Age of Artificial Intelligence. As artificial intelligence reshapes contemporary creative practices, this special edition invites educators, researchers, practitioners, and cultural leaders to critically examine how AI is redefining artistic production, educational methodologies, heritage preservation, and institutional management across the visual and performing arts. In recent years, AI has evolved from a technological tool into a profound cultural and pedagogical mediator. The selected papers in this issue reflect this transition with remarkable depth and interdisciplinary insight. They explore a wide range of themes—from AI-driven digital storytelling, generative art, and neural aesthetics to folk art preservation, digital twins in sculpture education, diffusion-model photography, and AI-enabled museum interactivity. Several contributions address pressing ethical and managerial concerns, including the governance of AI-generated artworks, deepfake risks, and the institutional challenges of integrating AI into academic and cultural ecosystems. A recurring emphasis across the submissions is the need to balance innovation with responsibility. Many authors foreground the pedagogical implications of AI: its potential to enrich learning environments, transform assessment methods, support creative talent identification, and expand access to cultural knowledge. Equally compelling are the studies that highlight AI’s role in sustainable art production, cloud-based creative management, virtual performances, interactive installations, and data-informed decision-making in media and art institutions. Submissions opened on 10 January 2025 and closed on 25 March 2025, attracting a substantial number of manuscripts from scholars and practitioners representing diverse domains—visual arts, performing arts, digital media, heritage studies, folk culture, sound design, design technology, and creative management. Each accepted paper underwent rigorous peer review to ensure the highest academic and ethical standards, resulting in a curated selection that reflects both the promise and complexity of AI in contemporary artistic practice. I extend my heartfelt gratitude to the contributors for their scholarly rigor, to our reviewers for their thoughtful evaluations, and to Granthaalayah Publications for their continued support in strengthening research dissemination in the arts and humanities. The breadth and quality of work featured in this issue affirm our collective commitment to understanding AI not merely as a technological force but as a transformative agent influencing culture, creativity, and education. As you explore the articles in this special issue, I hope they inspire critical reflection, informed dialogue, and new directions for research and practice. May this volume contribute meaningfully to the evolving discourse on how artificial intelligence is shaping the future of art, media, and cultural pedagogy. Issue Editor: Dr. Kumkum Bharadwaj Professor (HOD) in Fine Arts, Maharani Laxmibai Girls P.G. College, Indore, India Email: drkumkum.bharadwaj@mp.gov.in Dr. C. Govindaraj Professor and Head, Department of English, Periyar University Centre for PG & Research Studies, India Email: drgovindpupgec@periyaruniversity.ac.in Dr. R. Devarajulu Reddy Professor of English, Department of Humanities and Basic Science, Sri Venkatesa Perumal College of Engineering and Technology, RVS Nagar, KN Road, Puttur, Tirupati District, Andhra Pradesh, India Email: drreddyvari@gmail.com Dr. A. Wati Walling Associate Professor in Sociology and Dean (Academic), NIT , Dimapur, Nagaland, India Email: watiwalling@nitnagaland.ac.in Dr. A. Noble Jebakumar Assistant Professor and Head, Department of English, Government Arts and Science College, Manapparai, India Email: drnoblejk@gmail.com